Addition of enzyme‐digested hydrolysed porcine mucosa to low‐fishmeal feed improves growth, intestinal microbiota, and intestinal peptide and amino acid transporter expressions in hybrid groupers (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂). (18th November 2020) - Yang, Xuanyi; Dong, Xiaohui; Yang, Qihui; Wang, Guanghui; Zhao, Xumin; Liu, Hongyu; Zhang, Shuang; Chi, Shuyan; Tan, Beiping
Abstract: In this study, five iso‐nitrogenous and iso‐lipidic experimental low‐FM diets were formulated with enzyme‐digested hydrolysed porcine mucosa (EH) at concentrations of 0 g/kg (EH0, controls), 30 g/kg (EH3), 60 g/kg (EH6), 90 g/kg (EH9) and 120 g/kg (EH12). Juvenile hybrid groupers ( n  = 450; initial body weight 7.50 ± 0.02 g) were randomly divided into 15 tanks and fed the experimental diets twice daily for 56 days. The weight gain rate, specific growth rate, protein efficiency rate, feed conversion rate and feed intake rate of group EH3 were not significantly different from those of controls. The villus length and muscle thickness of the distal intestine (DI) in group EH12 and the villus width of the proximal intestine (PI) in group EH6 were significantly higher than those in controls. The Shannon index was significantly higher in group EH6 than in other groups. Group EH6 exhibited 17 pathway subclasses with significant differences to the other groups, comprising organismal systems (4), human diseases (6), cellular processes (2), metabolism (4) and environmental information processing (1). The expressions of CAT1, CAT2, LAAT1 and SNAT3 in the PI, and PAT1, B 0 AT3 and B0, +AT in the mid intestine (MI), and EAAT1 and PepT1 in the PI and MI in group EH6 were significantly higher than those in controls. The expressions of CAT1, CAT2, LAAT1, PAT1, SNAT3, EAAT1, B 0, + AT and PepT1 in the DI of group EH3 were significantly greater than those in controls. The maximum amount of EH that could be added to low‐FM feed to improve the digestive enzyme activity and amino acid and small peptide transport ability of the DI without obviously affecting the growth performance of hybrid groupers was 30 g/kg. EH contents ≥ 60 g/kg had negative impacts on growth performance and feed efficiency.